Linear childhood discoid lupus erythematosus along a Blaschko's line of the arm - Tetsuo Toyama; Takuya Miyagawa; Shinichi Sato; Yoshihide Asano (Frontiers Media S.A., 2022)
Abstract Linear childhood discoid lupus erythematosus (DLE) is a rare variant of DLE with a linear distribution that preferentially occurs on the face and scalp of children. We report a rare case of linear childhood DLE on the Blaschko's line of his left upper arm of a 7‐year‐old Japanese boy with 4‐year history of the disease. He was positive for anti‐single‐stranded DNA antibodies, but still showed no systemic symptoms during the 3‐year follow‐up period. We reviewed previous reports on linear childhood DLE and found that patients with nonfacial/nonscalp skin lesions are significantly more likely to be positive for autoantibodies.